2018
DOI: 10.5897/ajar2015.9847
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Grafting Techniques and their Effects on some Growth Parameters of Ten Elite Cocoa Clones (Theobroma cacao L.)

Abstract: Cocoa productivity in Côte d'Ivoire has been on a downward trend for the last decades due to many factors key among them being the non-availability of quality planting materials. However, some elite clones developed in the country are available and need to be adopted by farmers. This study was conducted in Soubré, Côte d'Ivoire to evaluate the grafting techniques (top grafting and budding) success of 10 elite cocoa clones and their effects on selected growth parameters in the nursery and field. Experimental de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 7 publications
2
6
1
Order By: Relevance
“…Therefore, according to the current work, to ensure a good resumption of the graft, it is necessary to do the grafting at an advanced age of the rootstock from three (3) months to 4-months in the nursery. The current results, in accordance to those of [ 11 , 22 ] could be explained by the fact that rootstocks of advanced age (3 months and 4 months) have a large reserve of hormones and can easily renew and regenerate their cells while that of 2-month-old with lower success could be attributed to the low carbohydrate reserves. Our results concur also to those of [ 14 , 36 ] who stated that rootstock age is affected by regenerating ability of plant slices due to the differential activity of meristematic cells.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Therefore, according to the current work, to ensure a good resumption of the graft, it is necessary to do the grafting at an advanced age of the rootstock from three (3) months to 4-months in the nursery. The current results, in accordance to those of [ 11 , 22 ] could be explained by the fact that rootstocks of advanced age (3 months and 4 months) have a large reserve of hormones and can easily renew and regenerate their cells while that of 2-month-old with lower success could be attributed to the low carbohydrate reserves. Our results concur also to those of [ 14 , 36 ] who stated that rootstock age is affected by regenerating ability of plant slices due to the differential activity of meristematic cells.…”
Section: Discussionsupporting
confidence: 92%
“…Graft success depends on the rootstock-scion physiological compatibility and the proper alignment of tissues in the graft union [ 22 , 38 ]. The low grafting success recorded for some clones implies a relative mortality rate of the cocoa clones' seedlings.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Combining different genotypes in the rootstock (the mother tree) and the scions, grafted on the pruned mother tree, may be optimized to maximize pollination success and fruit set (Vansynghel, Ocampo‐Ariza, Maas, Martin, Thomas, Hanf‐Dressler, Schumacher, Ulloque‐Samatelo, Tscharntke, et al., 2022 ). Grafting of old trees can be easily performed with standard grafting practices (Daouda et al., 2018 ), and field experiments with Piura white cacao (Ocampo‐Ariza et al., 2022 ) showed that after ca. 2 years yield levels can be 40%–80% higher than in non‐grafted neighboring trees (unpublished data).…”
Section: Selection and Implementation Of The Best Native Cacao Varietiesmentioning
confidence: 99%